Technical and Financial Study of Capture Business Mantis Shrimp (Harpiosquilla raphidea) Using Base Nets Driven in Kepenghuluan Sinaboi Sinaboi District Rokan Hilir Regency Riau Province - Syahrul, Syahrul; Zain, Jonny; Bustari, Bustari (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
This research was conducted in September 2019 in Sinaboi Waters, Rokan Hilir Regency, Riau Province. This study aims to analyze the technical and financial aspects of catching mantis shrimp (Harpiosquilla raphidea) in drift bottom fishing gear. The method used is survey method and case study. The fishing fleet used is 1 ship with a weight of 3 GT, which has a 27 HP propulsion engine. The results of the technical analysis, the main catch of the bottom drift net fishing gear is mantis shrimp using bait and obtained an upper hanging ratio of 0.55; hanging ratio down by 0.45 and shortening by 55%. The results of the calculation of business feasibility analysis show the total investment value of the fishing business is Rp.46,622,000 with a BCR value of 1.2, an FRR value of 39.53%, and a PPC value of 2.5 which means the time required by fishermen to The payback period is 2 years 5 months. Therefore, it can be concluded that the fishing effort is feasible to run and develop